Comprehensive dental therapy (periodontal and exodontia) removes inflammatory foci and aids in glycemic control - Arthur H. Friedlander (Blackwell Synergy, 2007)
Staff Oral and Maxillofacial Surgeon/ Associate Chief of Staff and Director of Graduate Medical Education,Veterans Affairs Medical Center at Los Angeles and Professor in Residence, Oral and Maxillofacial Surgery, University of California Los Angeles Dental School and Director of Quality Assurance, Dental Service, UCLA Medical Center, Los Angeles, CA, USA